TLRs, Treg, and B Cells, an Interplay of Regulation during Helminth Infection - Layland, Laura E.; Ludwig-Portugall, Isis (Frontiers in Immunology, 2012)
Commonly described as masters of regulation parasitic helminth infections provide a fascinating insight into the complexity of our immune system. As with many other pathogens helminths have developed complex evasion strategies and the immune response of the host has to find a balance between eliciting severe damage to eliminate the parasite or limiting damage and thereby accepting the infection. Nevertheless, one should not forget that these infections still pose a serious public health problem and can elicit severe disfigurement or death in the individual. An interesting spin-off of helminth manipulation on host responses is the apparent prevention of autoimmune diseases or allergy although the actual mechanisms remain unclear. It is well known that Toll-like-receptors (TLR) and non TLR PRRs play a critical role in initiating innate immune responses which in turn create appropriate adaptive immune reactions. Helminths comprise of a multitude of (glyco)-proteins and (glyco)-lipids and some have been shown to trigger TLR, or alter TLR-mediated responses. Such reactions of course alter adaptive immunity as well. This review will address the consequences of TLR-triggering by helminth antigens and the downstream effect on B cell and regulatory T cell (Treg) actions.